Penggunaan Bahasa Persuasif dalam Buku Pengayaan Digital Literasi: Pendekatan Retorika terhadap Tema Eco Green - Sumirah, Sumirah; Zulaeha, Ida; Mardikantoro, Hari Bakti; Haryadi, Haryadi (Aksara, 2025)
This study analyzes the use of persuasive language in eco-green literacy digital enrichment books for junior high school students through a rhetorical approach. By combining critical discourse analysis (CDA) and classical rhetorical theory (pathos, logos, ethos), this study identifies effective linguistic strategies in conveying environmental messages. The research method uses a descriptive qualitative approach with a case study design. Data collection techniques include: (1) document analysis of 15 eco green digital books for junior high schools, (2) in-depth interviews with 12 students and 8 teachers, (3) participatory observation during the implementation of teaching materials for 3 months, and (4) focus group discussions (FGD) with linguistics and environmental education experts. Data analysis was carried out through triangulation of methods using the Miles & Huberman model (data reduction, data display, verification) combined with Aristotle's rhetorical analysis framework and thematic coding techniques to identify linguistic persuasive patterns. The results of the study show that the combination of emotional narrative (pathos), scientific facts (logos), and source credibility (ethos) successfully builds students' ecological awareness, improves conceptual understanding, and encourages real action. Concrete examples such as the story "The Magic Switch in Class 7A", metaphors ("The Earth is our home"), and calls to action ("Turn off the lights!") have proven effective in creating emotional engagement and behavior change. These findings reinforce the theory of the Elaboration Likelihood Model (Petty & Cacioppo, 1986) and provide practical recommendations for digital teaching material developers: integration of holistic rhetorical strategies, emphasis on empirical experience, and adaptive content design for the digital native generation. This research contributes to strengthening environmental literacy through a linguistic-rhetorical approach that is relevant to the challenges of 21st century education.  AbstrakPenelitian ini menganalisis penggunaan bahasa persuasif dalam buku pengayaan digital literasi bertema eco green untuk siswa SMP melalui pendekatan retorika. Dengan menggabungkan analisis wacana kritis (CDA) dan teori retorika klasik (pathos, logos, ethos), studi ini mengidentifikasi strategi linguistik yang efektif dalam menyampaikan pesan lingkungan. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Teknik pengumpulan data meliputi: (1) analisis dokumen terhadap 15 buku digital eco green untuk SMP, (2) wawancara mendalam dengan 12 siswa dan 8 guru, (3) observasi partisipatif selama implementasi bahan ajar selama 3 bulan, dan (4) focus group discussion (FGD) dengan ahli linguistik dan pendidikan lingkungan. Analisis data dilakukan melalui triangulasi metode menggunakan model Miles & Huberman (reduksi data, display data, verifikasi) yang dikombinasikan dengan framework analisis retorika Aristoteles dan teknik coding tematik untuk mengidentifikasi pola persuasif linguistik. Hasil penelitian menunjukkan bahwa kombinasi narasi emosional (pathos), fakta ilmiah (logos), dan kredibilitas sumber (ethos) berhasil membangun kesadaran ekologis siswa, meningkatkan pemahaman konseptual, serta mendorong aksi nyata. Contoh konkret seperti cerita "Saklar Ajaib di Kelas 7A", metafora ("Bumi adalah rumah kita"), dan call to action ("Matikan lampu!") terbukti efektif menciptakan emotional engagement dan perubahan perilaku. Temuan ini memperkuat teori Elaboration Likelihood Model (Petty & Cacioppo, 1986) sekaligus memberikan rekomendasi praktis bagi pengembang bahan ajar digital: integrasi strategi retorika yang holistik, penekanan pada pengalaman empiris, dan desain konten yang adaptif bagi generasi digital native. Penelitian ini berkontribusi pada penguatan literasi lingkungan melalui pendekatan linguistik-retoris yang relevan dengan tantangan pendidikan abad ke-21.